Forests as safety nets for mitigating the impacts of HIV/AIDS in southern Africa - Shackleton, S.; Kaschula, S.; Twine, W.; Hunter, L.; Holding-Anyonge, C.; Petheram, L. (Center for International Forestry Research, 2006)
HIV/AIDS is having devastating impacts around the world, with southern Africa being particularly hard hit. Significant numbers of households and families in this region are undergoing dramatic social and livelihood change and suffering extreme poverty as a consequence of this disease. Recent studies suggest that forests can act as safety nets to help mitigate the negative impacts of HIV/AIDS and boost food security. However, we need to ensure that forest contributions are recognised and supported by governments, policy makers, donors, development organisations and markets.